The sunshine vitamin D: ubiquitous source, still so deficient in mother and baby duo - K., Shilpa S.; Fatima, Naima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Vitamin D is a fat-soluble vitamin, a sunshine vitamin. Vitamin D deficiency is now recognized as a pandemic. Fetus depends on mother for its need of vitamin D, thus there is growing concern for its impact on neonates. This study was designed to determine the correlation between 25-hydroxyvitamin D (vitamin D3) levels in maternal blood and in cord blood. Methods: A total 50 term pregnant women attending antenatal clinic at SVS medical college, Telangana and their neonates were included in the study. At term after taking written consent, maternal and cord blood vitamin D3 were measured, and values were correlated. Antenatal and neonatal complications were noted, and correlated with vitamin D3 levels. Results: In this study 80% of pregnant women and 88% of neonates were vitamin D3 deficient. Mean maternal blood vitamin D3 was 17.62±10.01 and cord blood vitamin D3 was 12.84±7.68. Maternal blood vitamin D3 correlated positively with cord blood vitamin D3 (r=0.951, p<0.001). Antenatal and neonatal complications were observed, but statistically significant association with vitamin D3 deficiency could not be established. Conclusions: This study has demonstrated a very high prevalence of vitamin D deficiency in apparently healthy, young, pregnant women despite abundant sunlight leading to deficiency in their neonates. To establish strong association between vitamin D3 deficiency and various antenatal and neonatal complications further studies with large subject groups are required.